Mental Health Services for Correctional Inmates at A Correctional Institution - Subandi Subandi; Ardian Praptomojati; Irgahayu Madhina; Mutia Aini Ahmad; Nur Firiyani Hardi; Resa Wuryansari (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
In Indonesia, the number of inmates increases almost every year. On the other hand, the Indonesian government is often faced with a limited number of existing prison facilities, including mental health services. Many cases of mental disorders in inmates are not treated, and their conditions even get worse. This program aimed to develop a mental health service program for inmates with individual counseling and supportive group therapy combined with the dhikr therapy in one of the prisons in Indonesia. Data were collected using questionnaires, interviews, and Focus Group Discussions (FGD). Questionnaires and interviews were conducted with the inmates, while the FGDs were conducted with psychologists. Data were analyzed descriptively for questionnaires and thematic analysis for interviews and FGDs. Based on the data collected, as many as 34 inmates used individual counseling services with a total of 50 visits. The data shows that the problems consulted in the form of family problems (59%), problems with partners (20%), prison environment problems (6%), fear of being released (6%), self-esteem problems (6%), and problems about a job (3%). The results of data analysis showed that the inmates feel that psychological interventions in prison were beneficial. Both inmates who had attended individual counseling and supportive group therapy combined with the dhikr therapy felt its benefits in overcoming the psychological problems. This study suggests that mental health services in prisons need to be an area of concern, considering the urgent needs in prisons.